2002
DOI: 10.1016/s0014-5793(02)02617-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in North and South America before Columbus

Abstract: We present a molecular epidemiologic study, based on an analysis of vacA, cagA and cag right end junction genotypes from 1042 Helicobacter pylori isolates, suggesting that H. pylori was present in the New World before Columbus. Eight Native Colombian and Alaskan strains possessed novel vacA and/or cagA gene structures and were more closely related to East Asian than to non-Asian H. pylori. Some Native Alaskan strains appear to have originated in Central Asia and to have arrived after strains found in South Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
134
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 23 publications
17
134
2
Order By: Relevance
“…DNA was extracted using the QIAamp DNA Mini Kit (QIAGEN, Inc. Santa Clarita, CA, USA) according to the manufacturer's instructions. The cagA genotypes (East-Asian type or Western type) and vacA genotypes (s region: s1a, s1b and s1c and m regions: m1a, m1b, m1c and m2) were evaluated by polymerase chain reaction (PCR) as previously described (Atherton et al, 1995;Yamaoka et al, 1998;Mukhopadhyay et al, 2000;Kersulyte et al, 2000;Ghose et al, 2002;Yamaoka et al, 2002). To confirm the results obtained by PCR and to determine the status of vacA m1c in case of vacA m1a, m1b and m2 were negative, PCR-based sequencing was also performed as previously described (Yamaoka et al, 2002).…”
Section: H Pylori Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted using the QIAamp DNA Mini Kit (QIAGEN, Inc. Santa Clarita, CA, USA) according to the manufacturer's instructions. The cagA genotypes (East-Asian type or Western type) and vacA genotypes (s region: s1a, s1b and s1c and m regions: m1a, m1b, m1c and m2) were evaluated by polymerase chain reaction (PCR) as previously described (Atherton et al, 1995;Yamaoka et al, 1998;Mukhopadhyay et al, 2000;Kersulyte et al, 2000;Ghose et al, 2002;Yamaoka et al, 2002). To confirm the results obtained by PCR and to determine the status of vacA m1c in case of vacA m1a, m1b and m2 were negative, PCR-based sequencing was also performed as previously described (Yamaoka et al, 2002).…”
Section: H Pylori Genotypingmentioning
confidence: 99%
“…The 3' repeat region of the cagA can be used as a marker to separate East Asia from those in Western countries. Interestingly, studies from Asian countries reported that this East-Asian cagA might be a subgenotype of cagA gene which plays important roles in gastroduodenal disease development (Yamaoka et al, 1998;Yamaoka et al, 1999, Yamaoka et al, 2000Yamaoka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches have focused on commensals and parasites that accompany human migrations, including viruses such as JC virus (20,21) and human T-lymphotrophic virus (22), fungi (23), rats (24), and the bacterium Helicobacter pylori (25)(26)(27). In the present study, we investigated the usefulness of H. pylori, a Gram-negative bacterium that persistently colonizes the stomach of Ͼ50% of humans, as a potential genetic marker for deciphering recent human migrations.…”
mentioning
confidence: 99%
“…H. pylori strains are highly diverse, and within all loci examined, both extensive polymorphism and multiple informative sites are present that can be used to construct phylogenies (14,15). In particular, specific genotypes associated with either Europe or East Asia have been recognized (14)(15)(16). Extensive studies have shown that the vacA s allelic types have a specific geographic distribution (15,16).…”
mentioning
confidence: 99%
“…In particular, specific genotypes associated with either Europe or East Asia have been recognized (14)(15)(16). Extensive studies have shown that the vacA s allelic types have a specific geographic distribution (15,16). In particular, the vacA s1c allele is present exclusively in persons originating from East Asia (15,(17)(18)(19).…”
mentioning
confidence: 99%